Antioxidant Potential of Several Food Ingredients in Al-Quran and Hadith on Inflammation Process in Covid-19 - Mutiara Nabilla Jusuf; Enny Rohmawaty; Arri Putri Intan Pratiwi; Pritha Pitaloka (Sean Institute, 2023)
Coronavirus first appeared in China. The coronavirus spread rapidly and swiftly became a global pandemic. The mortality rate of this disease is known to be related to the pathobiological processes that occur and the increased pro-oxidant response. Antioxidants are required to maintain the balance of processes that occur in the body. Al-Quran and Hadith mention several food ingredients that have the potential as antioxidants. The literature review of published journals spanning 2010–2020 was reviewed with the topic of information related to the antioxidant potential of food ingredients in the Al-Quran and Hadith on the inflammatory process of COVID-19.